High-impact loading training induces bone hyperresorption activity in young elite female gymnasts - Jaffre, C.; Courteix, D.; Dine, G.; Lac, G.; Delamarche, P.; Benhamou, L. (Journal of Pediatric Endocrinology and Metabolism, 2001)
The aim of this study was to investigate the effect of intensive exercise on bone turnover (as reflected by bone resorption) in young elite female gymnasts. Forty-five healthy girls including 24 gymnasts (11.9+/-2 yr) and 21 controls (12.3+/-1.4 yr) were studied. Body weight, height, bone age and body composition were measured. Bone mineral density (BMD) was assessed at the whole body, lumbar vertebrae, hip and radius by means of DXA. Volumetric density (BMAD) was calculated. Bone velocity (SOS) and attenuation (BUA) were measured by QUS at the calcaneus. Urinary androstenedione (delta4), dehydroepiandrosterone sulfate (DHEA-S), and CrossLaps (CTx) were measured. BMD and BMAD were significantly greater in the gymnasts at all sites except whole body. SOS was found significantly higher. Delta4 values were significantly lower in the gymnasts. The distribution of the subjects according to Tanner stages was not different between groups. CTx levels were significantly higher in the gymnasts (989.08+/-154.63 microg/mmol Cr.) vs controls (580.25+/-123.99 microg/mmol Cr., p=0.02). CTx values decreased from Tanner stage 1 to stage 4 in each group, the gymnasts' levels always being higher than those of the controls. In conclusion, gymnastics seems to stimulate bone resorption activity in highly-trained young females. The coexistence of bone hyperresorption and higher BMD in gymnasts suggests increased bone turnover resulting in increased bone density in these subjects.